Landscape Education Two Decades after the European Landscape Convention-A Study with Trainee Teachers - José Manuel Crespo Castellanos; Carlos Martínez-Hernández; María Rosa Mateo Girona; Ayar Rodríguez de Castro (MDPI AG, 2023)
The European Landscape Convention promotes the protection, management and planning of landscapes and organises international co-operation on landscape issues. Member states committed to implement measures such as promoting social education about landscapes. The convention stated that, although it was part of the education curricula in some countries, landscape education was to be expanded from a multidisciplinary perspective. The Education Act in force in Spain in 2008 (LOE, 2007), when the convention was ratified, included landscape in the syllabus, but not from as broad a perspective as that reflected in the ELC. Later education reforms have gradually increased the presence of the landscape in school curricula. This study examines landscape-related knowledge and awareness among current trainee primary school teachers, whose whole education has occurred under the umbrella of the ELC. This aims to assess whether the ELC's targets have been met in terms of social awareness of landscape issues. A mixed questionnaire was designed, validated, and implemented in a sample of 322 students studying subjects related to the teaching of geography. The answers were analysed with descriptive and inferential statistics. The results reflect poor landscape-related knowledge and awareness, suggesting that the educational measures implemented since the ratification of the ELC have not been successful.